Distribution of Bacterial Endophytes in the Non-lesion Tissues of Potato and Their Response to Potato Common Scab - Shi, Wencong; Su, Gaoya; Li, Mingcong; Wang, Bing; Lin, Rongshan; Yang, Yutian; Wei, Tao; Zhou, Bo; Gao, Zheng (Frontiers in Microbiology, 2021)
The response of plant endophytes to disease within infected tissues has been well demonstrated, but the corresponding response of endophytes in non-lesion tissues remains unclear. Here, we studied the composition and distribution of bacterial endophytes in potato roots (RE), stems (SE) and tubers (TE), and explored the response of endophytes in non-lesion tissues to potato common scab (PCS) which is a soil-borne disease caused by pathogenic Streptomyces and results in serious losses to the global economy every year. Via high-throughput sequencing, the composition of endophytes in roots, stems and tubers had significant differences (P < 0.05) and the distribution of the bacterial communities illustrated a gradient from soil to root to tuber/stem. PCS significantly reduced bacterial endophytes α-diversity indexes, including ACE and the number of observed operational taxonomic units (OTUs), of RE without significantly reducing the indexes of SE and TE. No significant effect on the composition of endophytes were caused by PCS in roots, tubers or stems between high PCS severity (H) and low PCS severity (L) infections at the community level, but PCS did have a substantial impact on the relative abundance of several specific endophytes. Rhizobium and Sphingopyxis were significantly enriched in root endophytes with low PCS severity (REL); Delftia and Ochrobactrum in stem endophytes with low PCS severity (SEL); and Pedobacter, Delftia and Asticcacaulis in tuber endophytes with high PCS severity (TEH). OTU62, a potential PCS pathogen in this study, was capable of colonizing potato tubers, roots and stems with few or no symptoms present. Co-occurrence networks showed that the number of correlations to OTU62 was higher than average in these three tissue types, suggesting the importance of OTU62 in endophytic communities. This study clarified the distribution and composition of potato endophytes in tubers, roots and stems, and demonstrated the response of endophytes in non-lesion tissues to PCS.